Degraded capability : the media and the Kosovo crisis - Hammond, Phil, 1964-; Herman, Edward S. (London ; Sterling, Va. : Pluto Press, 2000)
'Required reading for anyone wishing to understand the war and the media's role in it.' The New Internationalist.
Foreword / Harold Pinter -- Introduction / Philip Hammond, Edward S. Herman -- Nato and the new world order : ideals and self-interest / Diana Johnstone -- Western intervention and the disintegration of Yugoslavia, 1989-1999 / David Chandler -- War crimes / Mirjana Skoco, William Woodger -- The war and its aftermath / Peter Gowan -- New militarism and the manufacture of warfare / Richard Keeble -- Nazifying the Serbs, from Bosnia to Kosovo / Mick Hume -- The military and the media / Mirjana Skoco, William Woodger -- Symbolic warfare : Nato versus the Serbian media / Goran Gocic -- Following Washington's script : the United States media and Kosovo / Seth Ackerman, Jim Naureckas -- CNN : selling Nato's war globally / Edward S. Herman, David Peterson -- Third way war : new Labour, the British media and Kosovo / Philip Hammond -- Censorship by omission / John Pilger -- The French media and the Kosovo war / Diana Johnstone -- From 'never again war' to 'never again Auschwitz' : dilemmas of German media policy in the war against Yugoslavia / Thomas Deichmann -- "Thank you God! Thank you Norway!' Norwegian newspapers and the Kosovo war / Karin Trandheim Ren -- The Greek 'participation' in Kosovo / Nikos Raptis -- Consensus and conflict in the Russian press / Philip Hammond, Lilia Nizamova, Irina Savelieva -- India : how India sees through Western reports / Raju G.C. Thomas -- An Indian view of the Western media from Iraq to Yugoslavia / Siddharth Varadarajan -- Conclusions : first casualty and beyond / Philip Hammond, Edward S. Herman.
Includes bibliographical references (pages 212-216) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Kosovo War, 1998-1999.; Kosovo War, 1998-1999 -- Press coverage; Kosovo War, 1998-1999 -- Mass media and the war; Kosovo War, 1998-1999 -- Propaganda; Guerre du Kosovo, 1998-1999.; Guerre du Kosovo, 1998-1999 -- Couverture de presse; Guerre du Kosovo, 1998-1999 -- Propagande; HISTORY -- General; SOCIAL SCIENCE -- Media Studies; Mass media and war; Press coverage; Propaganda; Kosovo (Republic); Serbia; Kosovo-Krieg; Massenmedien; Massamedia; Oorlogen; Berichtgeving; Oorlogspropaganda; 1998-1999; History